Quality of life of patients with osteoarthritis - A. E. Mihailova; V G Krivoshapkin; R N Prolopopova; Sh F Erdes (Научно-практическая ревматология)
Objective. To assess quality of life (QL) of pts with osteoarthritis (OA) in the city of Yakutsk. Material and methods . 100 outpts with OA (50 with knee and 50 - with hand OA) were included. QL was assessed with SF-36 in comparison with a population group (500 residents of comparable age and sex). Results. Role physical functioning state in pts was 2 times decreased in comparison with control group. Significant direct correlation between physical activity indices and age of pts was revealed. Significant sex differences of QL assessment results were shown. Conclusion. OA exerts negative influence on human physical, psychological and social functioning.